The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph182413374
|View full text |Cite
|
Sign up to set email alerts
|

The Sustained Psychological Impact of the COVID-19 Pandemic on Health Care Workers One Year after the Outbreak—A Repeated Cross-Sectional Survey in a Tertiary Hospital of North-East Italy

Abstract: This study aimed to evaluate the mental health outcomes of health care workers (HCWs) of the Verona academic hospital trust (Italy) one year after the outbreak of COVID-19 and to identify predicted risk factors. A web-based survey was conducted from mid-April to mid-May 2021 on hospital workers one year after the first evaluation performed during the lock-down phase of the COVID-19 pandemic. Post-traumatic stress, general anxiety, depression, and burnout were assessed by using, respectively, the impact of even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(95 citation statements)
references
References 42 publications
7
83
1
4
Order By: Relevance
“…A replication cross-sectional study one year after the COVID-19 outbreak to assess the mental health outcomes of HCW (n = 1 033) at an academic hospital in Verona (Italy) found that the percentage of HCW above the cut-off point increased from 2020 to 2021 across all performance domains (anxiety, 50.1% vs. 55.7, p < 0.05; depression, 26.6% vs. 40.6%, p < 0.001). In turn, a multivariate analysis showed that one year after the COVID-19 outbreak, nurses were more likely to experience anxiety and depression than other HCWs [51].…”
Section: Discussionmentioning
confidence: 99%
“…A replication cross-sectional study one year after the COVID-19 outbreak to assess the mental health outcomes of HCW (n = 1 033) at an academic hospital in Verona (Italy) found that the percentage of HCW above the cut-off point increased from 2020 to 2021 across all performance domains (anxiety, 50.1% vs. 55.7, p < 0.05; depression, 26.6% vs. 40.6%, p < 0.001). In turn, a multivariate analysis showed that one year after the COVID-19 outbreak, nurses were more likely to experience anxiety and depression than other HCWs [51].…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, a second evaluation is foreseen during the next SItI national congress that will be held in Padua in November 2022, as part of a repeated two-point cross-sectional survey. This methodology has been already used in previous stud-ies, enabling to follow variations over time in the response of HCWs to the pressure posed by the COVID-19 pandemic [13][14][15]. Third, due to the reference population considered, the findings cannot be extended to the whole population of HCWs in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that HCWs living in the most affected regions had a prevalence of psychological distress higher than their colleagues from the rest of the country; moreover, significant differences related to life changes were associated with the lockdown [12]. Another study revealed that one year after the beginning of COVID-19 emergency, Italian nurses were at the greatest risk of anxiety and depression, whereas residents were at the greatest risk of burnout, and working in intensive care units was associated with an increased risk of developing severe emotional exhaustion and a cynical attitude towards work [13].…”
Section: Introductionmentioning
confidence: 99%
“…As new variants emerge, HCWs must continue to serve COVID-19 and non-COVID patients while still fulfilling personal commitments for their families and themselves[14-16]. Burnout, emotional exhaustion, mental distress, depression and psychological stress have been linked to HCWs during this pandemic, and research continues to reveal high rates of infection [17]. In addition to patient care, HCWs must keep up with any developments in relation to emerging variants and their effects on clinical presentation, management, and measures of prevention—mainly vaccination and infection prevention practices[18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout, emotional exhaustion, mental distress, depression and psychological stress have been linked to HCWs during this pandemic, and research continues to reveal high rates of infection [17].…”
Section: Introductionmentioning
confidence: 99%